Perfil Hematológico e Bioquímico Sérico de Ovinos Infectados com Nematóides e Medicados com Ivermectina e Closantel - Costa, Kizzy Millenn de Freitas Mendonça (Universidade Federal Rural do Semi-Árido, 2011)
Despite its known resistance, the sheep are subject to endoparasitoses, which are the main limiting factor for its production worldwide, especially in tropical regions. This study aims to evaluate the changes in parasitic load, serum biochemical and hematological panel, and Famacha scores of mixed-bred sheep naturally infected with nematodes and treated with ivermectin and closantel. The study was conducted at July 2010, in a farm in the municipality of Mossoró, Rio Grande do Norte state, Brazil. We selected 41 animals were divided into three groups: group I- control (without treatment), group II- treated with ivermectin (0.2 mg/kg), and Group III- treated with closantel (5 mg/kg). Stool samples were collected on days 0, 7, 14 and 21 after treatment for quantitative analysis (EPG) and qualitative analysis (stool culture), we used samples from days 0, 14 and 21. The first blood sample was given on day 0, the second and third 24 and 72 hours after the first, respectively the fourth and fifth 7 and 14 days after the first of which analyzed the blood count, serum total protein, albumin and globulins, and albumin/globulins ratio. Famacha scores were determined the degree of each animal at all times of sampling. Closantel administration was effective for the reduction of parasite counts, especially Haemonchus contortus, in evaluated sheep. On the other hand, there was parasite resistance to ivermectin. Famacha data showed negative correlation with packed cell volume, leukocytes, hemoglobin, albumin, total protein, globulin and albumin/globulin ratio. The packed cell volume showed a strong and positive correlation with hemoglobin, albumin and total protein. Treatment with ivermectin and closantel were not responsible for considerable changes in hematological and biochemical parameters evaluated.
Hematologiy And Serum Biochemical Panel Sheep Infected with Nematodes and Dosed with Ivermectin and Closantel
Keywords: Sheep diseases; parasitary diseases; antihelmintics; parasite resistance; Doenças de ovinos; doenças parasitárias; anti-helmínticos; resistência parasitária; CIENCIAS AGRARIAS::MEDICINA VETERINARIA